2008
DOI: 10.1007/s10571-008-9270-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Oxidative Stress and Dysfunction in Rat Brain Induced by Carbofuran Exposure

Abstract: Repeated low-dose exposure to carbofuran exerts its neurotoxic effects by non-cholinergic mechanisms. Emerging evidence indicates that oxidative stress plays an important role in carbofuran neurotoxicity after sub-chronic exposure. The purpose of the present study is to evaluate the role of mitochondrial oxidative stress and dysfunction as a primary event responsible for neurotoxic effects observed after sub-chronic carbofuran exposure. Carbofuran was administered to rats at a dose of 1 mg/kg orally for a peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 43 publications
1
33
0
1
Order By: Relevance
“…Kaur et al (2007) showed that MDA levels were increased in the rat brain mitochondria following chronic administration of DDVP. We have also observed increased oxidative stress in mitochondria of carbofuran exposed brain resulting in cognitive and memory deficits (Kamboj et al 2008). Accumulation of peroxidation products in mitochondria leads to a decrease in electron transport that may impair cellular energy metabolism and viability (Orrenius et al 2007).…”
Section: Discussionmentioning
confidence: 82%
“…Kaur et al (2007) showed that MDA levels were increased in the rat brain mitochondria following chronic administration of DDVP. We have also observed increased oxidative stress in mitochondria of carbofuran exposed brain resulting in cognitive and memory deficits (Kamboj et al 2008). Accumulation of peroxidation products in mitochondria leads to a decrease in electron transport that may impair cellular energy metabolism and viability (Orrenius et al 2007).…”
Section: Discussionmentioning
confidence: 82%
“…MTT assay (Kamboj et al, 2008) A main application of MTT assay is to assess the viability (cell counting) and the proliferation of cells. 500 ul MTT (0.1 mg/ml) was added to 500 ml of mitochondrial preparation.…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…Shilajit reversed the CFS-induced decrease in ATP synthase activity, thereby providing the much needed ATP to meet the increased CFS-induced energy demands. MTT reduction to formazan blue has been used to assess mitochondrial respiration (Kamboj et al, 2008). MTT reduction studies showed that CFSinduced decrease in mitochondrial respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of MTT reduction. MTT reduction was measured by estimating formazan formed at 595 nm (Kamboj et al, 2008). 2.7.3.…”
Section: Estimation Of Cytochrome Oxidase (Complex-iv) Activitymentioning
confidence: 99%